Tinjauan Kelengkapan Pengisian Formulir Assesment Awal Poli Klinik Pasien Rawat Jalan Menggunakan Metode IAR - Dinda Melani Safitri; Puteri Fannya; Laela Indawati; Deasy Rosmala Dewi (Publikasi Indonesia, 2022)
The hospital is one of the health care facilities with various services helping people who have health probems. Medical record is a file that contains records and data related to patient identity, examination results, treatment history that has been given, other actions and services that have been carried out to patients. This study aimed to describe the completeness of filling the initial polyclinic assessment form. The methode of this study was descriptive analysis. The population of this study were the initial assessment of the physiotherapy clinic 312 medical records, surgery poly 177 medical records, and internal medicine clinic 457 medical records. And the sample of this research is 91 medical records. The results showed that from 91 medical records, 70 (77%) of forms is complete and 21 (23%) of forms is incomplete, which consisted of complete patient identification 80 (88%) and incomplete 11 (12%), completeness of important reports/notes 54 (59%) and incomplete 37 (41%), completeness of author authentication 73 (80%) and incomplete 18 (20%), and completeness of good records 72 (79%) and incomplete 19 ( 21%).